STRATEGIC EMPOWERING COMMUNITIES THROUGH ENERGY SECTOR CSR: A STUDY ON SUSTAINABILITY AND SOCIAL IMPACT - Rudy Tobing; M. Rezki Oktavianoor; Arief Yulianto (Graduate Program of Universitas Tarumanagara, 2025)
This study explores how corporate social responsibility (CSR) in the energy sector can move beyond short-term aid to become a strategy for long-term community empowerment. Using a qualitative case study of the ME–Rumah Asri program in Hilir Muara Village, the research positions women as central agents of change. The study aims to map the empowerment process, assess the social, economic, and environmental outcomes experienced by residents, and link them to the Sustainable Development Goals (SDGs 8, 11, and 17). Data were gathered through in-depth interviews and document analysis; thematic analysis was applied by extracting core ideas, clustering them into themes, articulating inter-theme linkages, and validating findings with informant while maintaining source triangulation and research ethics. The findings highlight three key insights. First, programs designed with early resident involvement foster self-confidence, strengthen decision-making capability, and build a sense of ownership. Second, tangible outcomes include additional household income, stronger social cohesion, and everyday pro-environment habits. Third, empowerment functions as the bridge between CSR interventions and sustainability outcomes, while reinforcing the company’s social legitimacy to operate. A noted challenge is initial dependence on corporate support; thus, a phased transition plan, stronger community/enterprise institutions, safe financing access, and diverse marketing channels are needed. Overall, when energy-sector CSR is framed as women-centered empowerment within cross-stakeholder partnerships, both social impact and sustainability improve, and program benefits endure.